Business organizations and collaborative web : practices, strategies and patterns - Malik, Kamna, 1967-; Choudhary, Praveen, 1974- (Hershey, PA : Business Science Reference, 2011)
'This book delves into identifying specific business processes and their linkage with the collaborative Web, while understanding the related implications for individuals, organizations and society'--Provided by publisher.
'Premier reference source'--P.1, cover.
Includes bibliographical references and index.
Keywords: Information technology -- Management; Web 2.0.; Internet; Online social networks